Storm Sudden Commencements Without Interplanetary Shocks - Wooyeon Park; Jeongwoo Lee; Yu Yi; Nicholas Ssessanga; Suyeon Oh (Journal of Astronomy and Space Sciences, 2015)
Storm sudden commencements (SSCs) occur due to a rapid compression of the Earth's magnetic field. This is generally believed to be caused by interplanetary (IP) shocks, but with exceptions. In this paper we explore possible causes of SSCs other than IP shocks through a statistical study of geomagnetic storms using SYM-H data provided by the World Data Center for Geomagnetism – Kyoto and by applying a superposed epoch analysis to simultaneous solar wind parameters obtained with the Advanced Composition Explorer (ACE) satellite. We select a total of 274 geomagnetic storms with minimum SYM-H of less than –30nT during 1998-2008 and regard them as SSCs if SYM-H increases by more than 10 nT over 10 minutes. Under this criterion, we found 103 geomagnetic storms with both SSC and IP shocks and 28 storms with SSC not associated with IP shocks. Storms in the former group share the property that the strength of the interplanetary magnetic field (IMF), proton density and proton velocity increase together with SYM-H, implying the action of IP shocks. During the storms in the latter group, only the proton density rises with SYM-H. We find that the density increase is associated with either high speed streams (HSSs) or interplanetary coronal mass ejections (ICMEs), and suggest that HSSs and ICMEs may be alternative contributors to SSCs.